Wealth into Power The Communist Party’s Embrace of China’s Private Sector - Dickson, Bruce J (Cambridge university Press, 2013)
After three decades of rapid economic growth in China, many observers believe that continued economic reform, and privatization in particular, is leading to eventual political change. China’s economic reforms are creating the independent sources of wealth, power, and influence that scholars have shown to be key factors in a country’s democratization. These economic and social changes have created expectations of a coming political change in China. Just as Chinese consumers have grown accustomed to freedom of choice in the market, they are also expected to begin demanding the right to choose their political leaders. China’s growing numbers of private entrepreneurs and urban middle class are also expected to push for the increased transparency and accountability that democracy provides